Do Consumer Confidence Indexes Help Forecast Consumer Spending in Real Time? - Dean Croushore (Deutsche Bundesbank, 2004)
Could a researcher or policy analyst use data reported from surveys of consumer confidence to improve forecasts of consumer spending? This issue has been examined in the literature previously, which reached the conclusion that consumer confidence helped improve the forecasts slightly. But that research was based on final, revised data and thus did not use the data that would have been available to forecasters in real time. This paper remedies that shortcoming, using the Real-Time Data Set for Macroeconomists to analyze the quality of forecasts made with indexes of consumer confidence. The main finding is that the indexes of consumer confidence are not of significant value in forecasting consumer spending. In fact, in some cases, they make the forecasts significantly worse.
Keywords: E27; 330; Konsumklima; Gesamtwirtschaftlicher Konsum; Prognoseverfahren; Schätzung; Theorie; Vereinigte Staaten